The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acscatal.1c03653
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Dimensionally Stable Anodes for Active Chlorine Generation

Abstract: RuO2 is one of the most important electrocatalyst materials as a key component of dimensionally stable anode (DSA) for chlorine evolution reaction, because of the high catalytic activity, while anodic corrosion remains a fundamental challenge that must be addressed. Here, we demonstrate that low-temperature annealing of RuO2 nanoparticles (∼1.7 nm) supported on Nb-doped TiO2 leads to the formation of durable active sites with superior activity and product selectivity toward active chlorine generation (10 mA cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Other uses for Nb-doped TiO 2 include photovoltaics and dye-sensitized solar cells. It also finds application in photocatalysis including for the production of H 2 , photoelectrochemical water splitting, and photocatalytic CO 2 reduction . Other catalytic applications are for catalyst supports, for example, for the oxygen reduction reaction and H 2 production, or for dimensionally stable anodes for the chlorine evolution reaction, and electrochemical destruction of “forever chemicals” . Nb-doped TiO 2 has potential application in batteries and supercapacitors including lithium-ion batteries , and Na-ion batteries .…”
Section: Introductionmentioning
confidence: 99%
“…Other uses for Nb-doped TiO 2 include photovoltaics and dye-sensitized solar cells. It also finds application in photocatalysis including for the production of H 2 , photoelectrochemical water splitting, and photocatalytic CO 2 reduction . Other catalytic applications are for catalyst supports, for example, for the oxygen reduction reaction and H 2 production, or for dimensionally stable anodes for the chlorine evolution reaction, and electrochemical destruction of “forever chemicals” . Nb-doped TiO 2 has potential application in batteries and supercapacitors including lithium-ion batteries , and Na-ion batteries .…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the active coating was investigated by XRD (Figure e). Compared with Ti substrate, the additional diffraction peaks of the Ti/RuO 2 porous electrode are attributed to rutile RuO 2 and TiO 2 . The detailed structural information on the coating was further investigated by TEM and SEAD.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with Ti substrate, the additional diffraction peaks of the Ti/RuO 2 porous electrode are attributed to rutile RuO 2 and TiO 2 . 32 The detailed structural information on the coating was further investigated by TEM and SEAD. The lattices with different structural orientations obtained from the TEM image were assigned to TiO 2 (110) and RuO 2 (101) planes (Figure 3f), and the SAED pattern also revealed that the diffraction spots corresponding to the TiO 2 (110) and RuO 2 (101) planes were clearly visible (SI Figure S12).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…By precisely regulating the fabrication parameters (Table S1), we constructed three kinds of nanostructure-decorated electrodes, including a slab with a large curvature radius of ∼200 nm, nanorods with a curvature radius of ∼25 nm, and nanoneedles with a small curvature radius of ∼10 nm (Figure a–c). As presented by the X-ray diffraction (XRD) pattern, some additional diffraction peaks of the electrodes were assigned to rutile TiO 2 and RuO 2 (Figure d) …”
Section: Results and Discussionmentioning
confidence: 99%
“…As presented by the X-ray diffraction (XRD) pattern, some additional diffraction peaks of the electrodes were assigned to rutile TiO 2 and RuO 2 (Figure 1d). 17 EDX exhibited a homogeneous distribution of Ti, O, and Ru on the surfaces of the electrodes (Figure 1e). Because the thickness of magnetron-sputtered Ru was only 20 nm, the EDX mapping signal of Ru was visibly weaker than that of Ti, with a Ru content of ∼0.2 g m −2 in the three electrodes.…”
Section: ■ Introductionmentioning
confidence: 99%